2015
DOI: 10.1088/1741-2560/13/1/016012
|View full text |Cite
|
Sign up to set email alerts
|

On the origins of the ‘global signal’ determined by functional magnetic resonance imaging in the resting state

Abstract: The present model shows that such correlations can arise as a consequence of the intermodular feedback connectivity without recourse to imposing a GS independent of the connectivity. Our model indicates that the GS reflects the extent of feedback pathways provided by the intermodular/inter-regional connections and hence the average correlation between modules or regions of cortex. However the model has not been used to elucidate the possible contributions of a GS independent of the connectivity, which might in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…This dominant mode of global BOLD co-variance is likely related to what is commonly described as the ‘global signal’ in resting-state fMRI studies, whose neurophysiological origin and role remains unclear 13, 5659 . Here, we find a clear relationship between the prevalence of FC state #1 and cognitive performance, pointing to a potential role of global BOLD coherence in cognitive processing.…”
Section: Discussionmentioning
confidence: 96%
“…This dominant mode of global BOLD co-variance is likely related to what is commonly described as the ‘global signal’ in resting-state fMRI studies, whose neurophysiological origin and role remains unclear 13, 5659 . Here, we find a clear relationship between the prevalence of FC state #1 and cognitive performance, pointing to a potential role of global BOLD coherence in cognitive processing.…”
Section: Discussionmentioning
confidence: 96%
“…In line with other studies employing the LEiDA method, PL 8 is a state of global phase coherence. This state has been assumed to reflect the global signal ( Bennett et al, 2016 , Cabral et al, 2017 , Keller et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to other studies using the LEiDA method, we found a state of global phase coherence in PL 8. While the exact function of this type of state is still unclear, it has been suggested to represent the global signal commonly found in fMRI studies ( Bennett et al, 2016 , Cabral et al, 2017 , Keller et al, 2013 ). Changes in the temporal characteristics of this state have been related to a variety of function and disfunction, including cognitive performance ( Cabral et al, 2017 ), depressive symptoms ( Alonso Martínez et al, 2020 , Figueroa et al, 2019 ), insight ( Larabi et al, 2020 ), and schizophrenia ( Farinha et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This then enables the calculation of the BOLD signal after input of a (scaled) neuronal activity. These equations have been used in a number of investigations of how the BOLD signal arises in neuronal networks (Bennett et al 2015(Bennett et al , 2016Deco et al 2014;Deco and Jirsa 2012;Robinson et al 2006). There is now considerable experimental evidence for negative BOLD signals (Devor et al 2007;Frahm et al 2008;Moraschi et al 2012;Mullinger et al 2014Mullinger et al , 2017Pasley et al 2007;Sadaghiani et al 2009;Shmuel et al 2006), but it is still an open question as to the role played by below-baseline neuronal activity.…”
Section: Introductionmentioning
confidence: 99%